Current knowledge of morbidities and direct costs related to diabetic foot disorders: a literature review - Waibel, Felix W. A.; Uçkay, Ilker; Soldevila-Boixader, Laura; Sydler, Christina; Gariani, Karim (Frontiers in Endocrinology, 2024)
Diabetes is a chronic disease associated with numerous complications including diabetic foot disorders, which are associated with significant morbidity and mortality as well as high costs. The costs associated with diabetic foot disorders comprise those linked to care (direct) and loss of productivity and poor quality of life (indirect). Due to the constant increase in diabetes prevalence, it is expected that diabetic foot disorder will require more resources, both in terms of caregivers and economically. We reviewed findings on management, morbidity, mortality, and costs related to diabetic foot disorder.